2001
DOI: 10.1128/jb.183.14.4382-4385.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Erythromycin Resistance Mutation in a 23S rRNA Gene, rrlA , of the Extreme Thermophile Thermus thermophilus IB-21

Abstract: Spontaneous, erythromycin-resistant mutants of Thermus thermophilus IB-21 were isolated and found to carry the mutation A2058G in one of two 23S rRNA operons. The heterozygosity of these mutants indicates that A2058G confers a dominant or codominant phenotype in this organism. This mutation provides a valuable tool for the genetic manipulation of the 23S rRNA genes of Thermus.Genetic analysis of rRNAs and ribosomal proteins has been an essential tool in elucidating the mechanism of protein synthesis. While num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…2; Table 1). While the T. thermophilus A2058G erythromycin resistance mutation was found only in the heterogeneous populations (21), in the present study, the A2059G and A2062G mutations were each found in both pure and mixed populations of ribosomes.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…2; Table 1). While the T. thermophilus A2058G erythromycin resistance mutation was found only in the heterogeneous populations (21), in the present study, the A2059G and A2062G mutations were each found in both pure and mixed populations of ribosomes.…”
Section: Resultsmentioning
confidence: 63%
“…Our ability to obtain a large number of rRNA mutants of T. thermophilus is made possible in part by the presence of only two rRNA gene copies. In our earlier search for rRNA mutants, we had obtained the A2058G mutation in 23S rRNA (21). All three isolates of this mutant that we examined proved to contain heterogeneous ribosome populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This species is also amenable to genetic manipulation (11,12), and antibiotic resistance mutations in ribosomal protein and rRNA genes are readily isolated (2,7,8). The ability to apply both genetics and X-ray crystallography to ribosomes from a single organism creates the exciting possibility of elucidating antibiotic resistance mechanisms at atomic level resolution.…”
mentioning
confidence: 99%